2022
DOI: 10.1007/s44211-022-00069-8
|View full text |Cite
|
Sign up to set email alerts
|

Luminol–hydrogen peroxide–horseradish peroxidase chemiluminescence intensification by kosmotrope ammonium sulfate

Abstract: The kosmotropic effect induced by ammonium sulfate (AS) at concentrations greater than approximately 2.8 M allows the marked intensification of chemiluminescence (CL) arising from a conventional luminol–hydrogen peroxide (H2O2)–horseradish peroxidase (HRP) reaction. Because of the kosmotropic effect, CL is intensified by at least three orders of magnitude than that from the conventional HRP-catalyzed luminol reaction with no AS; the linear relationship between the CL intensity and the HRP concentration is esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This increased generation of CL is known as enhanced CL and several CL enhancers are available for the HRP-luminol-H 2 O 2 reaction. Enhanced CL HRP-luminol-H 2 O 2 reaction has been applied widely for the detection of various substances [ [21] , [22] , [23] , [24] ]. Previous studies revealed that the use of 4-(1,2,4-triazol-1-yl)phenol (TRP) as a CL enhancer provided more intense, prolonged, and stable light emissions in developing CLIA [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…This increased generation of CL is known as enhanced CL and several CL enhancers are available for the HRP-luminol-H 2 O 2 reaction. Enhanced CL HRP-luminol-H 2 O 2 reaction has been applied widely for the detection of various substances [ [21] , [22] , [23] , [24] ]. Previous studies revealed that the use of 4-(1,2,4-triazol-1-yl)phenol (TRP) as a CL enhancer provided more intense, prolonged, and stable light emissions in developing CLIA [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…4), which is ascribed to the superiority of HRP-luminol-H 2 O 2 chemiluminescence as a detection system. 28,29 Both methods showed higher sensitivity and lower detection limits compared to previously reported immunoassays (Table 2). Furthermore, there was no cross-reaction with structural analogues of MT (CR% ≤ 0.001%, Table S1†).…”
Section: Discussionmentioning
confidence: 74%
“…Various compounds have been utilized as signal enhancers in the development of HRP-based CLEIAs, resulting in enhancement of CL and yield more long-lasting, and stable light emission. [26][27][28] Previous research 29 has demonstrated that 4-(imidazol-1-yl)phenol (IMP) as a CL enhancer exhibits enhanced light emissions that are more intense, prolonged, and stable when developing CLEIAs. Therefore, the HRP-luminol-H 2 O 2 -IMP reaction was chosen and implemented as the detection system in the CLEIA described in this article.…”
Section: Strategy For Cleia Developmentmentioning
confidence: 99%